Regulating emotional responses to aphasia to re‐engage in life: a qualitative interview study. Issue 2 (3rd February 2022) - Manning, Molly; MacFarlane, Anne; Hickey, Anne; Galvin, Rose; Franklin, Sue
Abstract: Background: People with post‐stroke aphasia (PWA) are more likely to experience serious mood disorders compared with those without. Emotional regulation may be important for influencing life participation after stroke. Understanding emotional regulation in the context of aphasia is important for promoting personally defined recovery, psychological well‐being and life participation. Aims: To explore how individuals experience and regulate negative emotional responses to aphasia as part of re‐engaging with life. Methods & Procedures: In‐depth semi‐structured qualitative interviews with 14 PWA were conducted. The focus and design were developed with public and patient involvement contributors. Reflexive thematic analysis was applied. Outcomes & Results: Analysis generated three themes, which captured inherent diversity across participants in terms of emotional experiences, responses and regulation strategies: (1) emotional upheaval at all stages of recovery; (2) regulating emotional upheaval; and (3) discerning possibilities for life participation. Emotional regulation occurred both within and without the context of formal support services. Conclusions & Implications: Individuals may be differently (en)abled in responding positively, with implications for aphasia psychological support and self‐management interventions. The findings may inform future interventions to optimize well‐being and personally meaningful outcomes for PWA. WHAT THIS PAPER ADDS: What is already known on the subject: PWA experience significant psychosocial upheaval and are at risk of mood disorders. Emotional regulation may be important for influencing one's emotional state, social participation and relationships after stroke. There is a need to better understand the ways in which PWA experience and regulate their emotions to develop better support for personally defined recovery. What this paper adds to existing knowledge: PWA may experience significant and pervasive mood disorders in the long term after stroke. This may be compounded by worries for their children's well‐being. Some, but not all, regulate emotions by drawing on positivity, determination, gratitude or stoicism. Having (supportive) opportunities to experience the impact of aphasia is important for discerning helpful strategies and participation opportunities. What are the potential or actual clinical implications of this work?: Confronting altered abilities requires supportive, responsive opportunities sensitive to emotional responses. Opportunities for peer support and/or meaningful emotional support and compassion from family and friends are important therapeutic targets. Therapeutic input should pay attention to any familial and parenting concerns that may be compounding low mood. Although emotional regulation and recovery may occur without formal support, mental health services must be organized in such a way that PWA can access as needed.